2015
DOI: 10.1007/s11032-015-0324-3
|View full text |Cite
|
Sign up to set email alerts
|

Association mapping and genomic prediction for resistance to sudden death syndrome in early maturing soybean germplasm

Abstract: Sudden death syndrome (SDS), caused by Fusarium virguliforme, has spread to northern soybean growing regions in the US causing significant yield losses. The objectives of this study were to identify loci underlying variation in plant responses to SDS through association mapping (AM) and to assess prediction accuracy of genomic selection (GS) in a panel of early maturing soybean germplasm. A set of 282 soybean breeding lines was selected from the University of Minnesota soybean breeding program and then genotyp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
46
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(48 citation statements)
references
References 63 publications
1
46
0
1
Order By: Relevance
“…Therefore, more regulatory genes in the loci are yet to be identified (Fig. A more recent GWAS study with rigorous greenhouse assay data found many fewer QTL of which 8 were previously report and ony 3 might be new (Bao et al, 2015). Moreover, on chromosome 7 near a SCN resistant loci (Rzd, resistance to zygote death), a cluster of associations within 0.7 Mbp interval was repeatedly detected with DS, DI, and DX (Wen et al, 2014).…”
Section: New Quantitative Trait Loci For Resistance Discovered By Assmentioning
confidence: 99%
“…Therefore, more regulatory genes in the loci are yet to be identified (Fig. A more recent GWAS study with rigorous greenhouse assay data found many fewer QTL of which 8 were previously report and ony 3 might be new (Bao et al, 2015). Moreover, on chromosome 7 near a SCN resistant loci (Rzd, resistance to zygote death), a cluster of associations within 0.7 Mbp interval was repeatedly detected with DS, DI, and DX (Wen et al, 2014).…”
Section: New Quantitative Trait Loci For Resistance Discovered By Assmentioning
confidence: 99%
“…For soybean, studies have reported genomic selection accuracy for production traits, development traits, or resistance to pathogens ( Jarquín et al, 2014;Bao et al, 2015;Zhang et al, 2016). Jarquín et al (2014) reported the prediction accuracies for yield and other agronomic traits obtained using genotyping-by-sequencing data.…”
mentioning
confidence: 99%
“…It is interesting that this region was also associated with resistance to P. sojae . The region on the chromosome 17 has the same location with a QTL identified in GWAS for resistance to Fusarium virguliforme (Bao et al, 2015;Zhang et al, 2015). SNP marker Gm17.8109237 identified in this study has located approximately 4 Mb from SNP marker ss715611120_C_T identified by J.…”
Section: Discussionmentioning
confidence: 51%
“…GWAS is based on use of whole genome genotyping and a detailed phytopathological and morphological description of collections with a high level of genetic diversity (Klein, 2007). A survey of recent reports has shown successful use of GWAS for studying soybean resistance to fungal diseases (Bao et al, 2015;Iquira et al, 2015;Schneider et al, 2016;Qin et al, 2017).…”
Section: Gwas Of a Soybean Breeding Collection From South East And Somentioning
confidence: 99%